Fernwood Then and Now: Community Green Map ... - Fernwood Neighbourhood Resource Group (University of Victoria Libraries, 2021)
A map showing the village of Fernwood today, marking food, music, art, gardens, services, and transportation. Reverse of map features historical pictures of the area; First Nations and early settler history to the region; a map from January 1863 focused on Fernwood, downtown Victoria, and surrounding areas; and pictures of flowers that were cultivated. This map is part of the Green Map System. ...